Szata roślinna rezerwatu Mierzwice (Nadleśnictwo Sarnaki) i jej ochrona - Krechowski, Janusz; Falkowski, Michał; Piórek, Katarzyna; Wierzba, Marek (Leśne Prace Badawcze, 2026)
The ‘Mierzwice’ nature reserve (forest district 206b, c and d of the Sarnaki Forest Inspectorate), situated in the area of the Podlaski Przełom Bug Landscape Park, is one of the most valuable natural assets of the central Bug river valley. The 12.98 ha reserve was established in 2010 to aid protection of the stand of xerothermic vegetation and its surrounding deciduous forest. In total, eight plant associations were identified within the reserve: Geranio-Peucedanetum cervariae , Geranio-Anemonetum sylvestris , Geranio-Trifolietum alpestris , Trifolio medii-Agrimonietum , Rubo fruticosi-Prunetum , Rhamno-Cornetum sanguinei, Potentillo albae-Quercetum and Tilio cordatae-Carpinetum betuli . Furthermore, 23 protected and 31 endangered species were found in the reserve including the following examples: Cephalanthera rubra , Thesium ebracteatum , Cypripedium calceolus , Gentiana cruciata , Anemone sylvestris , Cimicifuga europaea , Viola rupestris , Crepis praemorsa , Asperula tinctoria , Stachys recta , Laserpitium latifolium . Over the last few years, a regression of the species diagnostic number for thermophilous oak forests and xerothermic grasslands has been observed as a result of succession and expansion of Calamagrostis epigejos . Active protection of xerothermic vegetation such as uprooting of trees and bushes, regular grazing or mowing has been suggested in order to prevent the expansion of Calamagrostis epigejos .